Making managerial decisions based on analysis of financial statements - S. P. Spiridonov; Yu. Yu. Podkhvatilina (Путеводитель предпринимателя, 2023)
Today, in a changing economic situation, an important condition for ensuring financial stability and maximizing profits for commercial organizations is tactical and strategic planning, based on a competent analysis of financial statements. Developing a management decision is considered one of the fundamental tasks of the enterprise management process. Analysis of the financial statements of a commercial organization allows you to assess the financial position, performance efficiency and prospects for its development, which helps to identify possible problems and propose ways to solve them. The authors substantiate the role of financial reporting analysis for making competent management decisions. The article analyzes the financial statements of PJSC «Pigment» for 2019–2021. The stages of making management decisions and the circumstances influencing them are also considered. An analysis of the main indicators of financial stability, liquidity and profitability of the enterprise indicates an increase in operating efficiency and a certain decrease in financial stability. Based on the analysis, effective management decisions are developed to overcome existing financial difficulties.